The influence of technology, environment and user acceptance on the effectiveness of information system project selection using SEM - --, Syaifudin; Abdullah, Che Sobry; Mohamed Udin, Zulkifli; Hassan, Mohamad Ghozali; Johari, Nor Azmi (IBIMA Publishing, 2013)
The selection of the present information system project is difficult because of the many factors that influence it. Information system project should pay attention to the user acceptance, technology and the environment in terms of their influence on the information system project selection.The purpose of this paper is to determine how much influence user acceptance, technology and the environment have on the information system project selection.This research uses data obtained from several ministries and analyzed using SEM (Structural Equation Models).The results found that the technology and the environment affects user acceptance. Moreover, technology and environment affect the effectiveness of the information systems project selection through the mediating effect of user acceptance. User acceptance, tested by the incorporation of usefulness and ease of use, the results are more modest and in line with previous theories. Furthermore, the external environment highly impacts the information system project selection.